Scoring Setting and Infrastructure di Kampus Politeknik Negeri Medan Berdasar UI Green Metric Guide Lines 2023 - Syahputra, Muhammad Taufiq; Rita, Eva; Carlo, Nasfryzal; Jumas, Dwifitra Y; Mulyani, Rini; Fuadi, Al-Busyra (Jurnal Talenta Sipil, 2025)
Green Campus is a concept that supports sustainable and environmentally sound development by involving the academic community in the campus environment. In its strategic plan, the Medan State Polytechnic (Polmed) campus proclaimed to become a green campus in 2025. The efforts made by the Polmed campus to participate in sustainable development and become a green campus are by participating in the UI Green Metric World University Ranking program. In this program, one of the assessment indicator is setting and infrastructure, with 11 assessment criteria; the ratio of open space to campus area, total campus area covered by forest vegetation, total campus area covered by plant vegetation, total campus area for water absorption, total open space area to campus population, percentage of campus budget for sustainable efforts, percentage of building operation and maintenance activities in one year, campus facilities for the disabled, special needs, security and safety facilities, health infrastructure, conservation programs. This study aims to determine the Polmed campus score on setting and infrastructure indicators. By using quantitative methods, the results showed that Polmed campus has 8 criteria out of 11 required criteria. The score obtained by Polmed campus is 440 out of 1500 points. To increase the score can be implemented; vertical garden or rooftop garden on plant vegetation criteria (SI 3), making biopore infiltration holes and replacing paving blocks with grass blocks on water catchment area criteria (SI 4), installing guiding blocks and making ramps for disabled facilities criteria (SI 8), and blocking space for emergency rooms and lactation rooms on Health infrastructure criteria (SI 10).